Make time for less-intense training - Faigenbaum, A. D.; McFarland, J. (Strength and Conditioning Journal, 2006)
Regular participation in a youth resistance training program may improve muscular fitness, may enhance athletic performance, and may reduce the likelihood of sports-related injuries (2). A growing number of boys and girls are participating in activities which strengthen or tone their muscles (1), and it is common for young athletes to supplement their sports training with resistance training. However, the weekly training schedule (combined sports practice, sports competition, and resistance training) of some high school athletes rivals those of college athletes. Nowadays, it is not uncommon for some high school athletes to participate in sports practice 4 or 5 days per week, compete once or twice per week, and resistance train 3 or 4 days per week. It appears that the importance of active rest and recovery is undervalued or misunderstood in some high school programs.